Optical Tunneling to Improve Light Extraction in Quantum Dot and Perovskite Light-Emitting Diodes - Guanding Mei; Dan Wu; Shihao Ding; Wallace C. H. Choy; Kai Wang; Xiao Wei Sun (IEEE Photonics Journal, 2020)
An effective strategy based on optical tunneling is developed to significantly improve the efficiency of quantum dots light-emitting diodes (QLEDs) and perovskite light-emitting diodes (PeLEDs). Contrary to the common impression that the hole transport layers (HTL) with low refractive index will severely confine lights according to Snell's law, optical tunneling unlocks a channel to extract the lights through HTL. In this work, we demonstrate the light beyond the critical angle still has a chance to penetrate into the substrate and finally emit outside the device. An optical tunneling model is also presented here to quantitatively describe the light extraction through optical tunneling and reveal related factors. Applying a thin HTL (thickness = 10 nm) and a high-index substrate (refractive index = 2) in the typical device architecture (Glass/ITO/PEDOT:PSS/EML/TPBi/LiF/Al), substrate modes can be improved from 18% to 60%. Therefore, optical tunneling followed by EES is believed to be a cost-effective strategy to enhance light extraction efficiency. This work unravels the potential to further significantly improve the efficiency of QLEDs and PeLEDs.